1993
DOI: 10.1007/bf00317517
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intraguild predation among generalist insect predators on the suppression of an herbivore population

Abstract: We evaluated the influence of intraguild predation among generalist insect predators on the suppression of an herbivore, the aphid Aphis gossypii, to test the appropriateness of the simple three trophic level model proposed by Hairston, Smith, and Slobodkin (1960). We manipulated components of the predator community, including three hemipteran predators and larvae of the predatory green lacewing Chrysoperla carnea, in field enclosure/exclosure experiments to address four questions: (1) Do generalist hemipteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
283
4
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(311 citation statements)
references
References 41 publications
12
283
4
9
Order By: Relevance
“…Several studies suggest that intraguild predation by generalists on specialist predators can lead to herbivore communities being released from predation (e.g., Rosenheim et al. 1993, Hodge 1999, Snyder and Ives 2001). However, our analysis would suggest that the combination of both generalist and specialist predators in polyculture treatments can lead to greater prey suppression than the mean of the component species.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that intraguild predation by generalists on specialist predators can lead to herbivore communities being released from predation (e.g., Rosenheim et al. 1993, Hodge 1999, Snyder and Ives 2001). However, our analysis would suggest that the combination of both generalist and specialist predators in polyculture treatments can lead to greater prey suppression than the mean of the component species.…”
Section: Discussionmentioning
confidence: 99%
“…As T. brassicae is searching efficiently in maize (Babendreier et al, 2003c), we hypothesised that the inundative releases of T. brassicae into maize fields may negatively affect populations of other beneficial insects present in maize, which could in turn lead to increasing pest populations and an increasing use of pesticides. Evidence for such adverse effects on pest control due to intraguild competitors is accumulating (e.g., Dinter, 1998;Yasuda & Kimura, 2001), and Rosenheim et al (1993) have also shown that the experimental addition of top predators such as Zelus renardii (Kolenati) (Hemiptera: Reduviidae) or Nabis spp. (Hemiptera: Nabidae) caused sufficient predation on C. carnea to release aphid populations from regulation.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, l'efficacité des ennemis naturels peut être affectée par des interactions négatives de type « prédation intraguilde », lorsqu'un ennemi naturel dévore un compétiteur (Lucas et al 1998). À titre d'exemple, dans les champs de coton aux États-Unis, des lâchers de chrysopes effectués pour réduire les populations du puceron du coton ont échoué parce que les prédateurs indigènes ont éliminé les chrysopes (Rosenheim et al 1993). Toutefois, les effets de la prédation intraguilde sur la lutte aux ravageurs ne sont pas nécessairement négatifs, particulièrement dans le cas d'une lutte « inoculative » où la prédation intraguilde peut contribuer à stabiliser le système (Rosenheim et al 1995).…”
Section: Le Défi De La Complexitéunclassified